Victoria - Guy, John. (Great Britain : ticktock Pub., 1998)
Photographs and text examine the life of Britain's Queen Victoria, and look at some of the significant events that occurred during her reign, from 1837 to 1901.
Includes index.
7.1
5-8
Keywords: Victoria, -- Queen of Great Britain, -- 1819-1901 -- Juvenile literature; Victoria, -- Queen of Great Britain, -- 1819-1901.; Victoria, -- Queen of Great Britain, -- 1819-1901.; Queens -- Great Britain -- Biography. -- Juvenile literature; Kings, queens, rulers, etc; Queens -- Great Britain -- Biography; Great Britain -- History -- Victoria, 1837-1901 -- Juvenile literature; Great Britain -- Kings and rulers -- Biography -- Juvenile literature; Great Britain -- History -- Victoria, 1837-1901.; Great Britain -- History; Great Britain -- Kings and rulers -- Biography